2007
DOI: 10.1021/jp066729x
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Formation of HCPH(X2A‘) Molecules in Extraterrestrial Environments:  Crossed Molecular Beam Study of the Reaction of Carbon Atoms, C(3Pj), with Phosphine, PH3(XA1)

Abstract: The reaction between ground state carbon atoms, C(3P(j)), and phosphine, PH3(X(1)A1), was investigated at two collision energies of 21.1 and 42.5 kJ mol(-1) using the crossed molecular beam technique. The chemical dynamics extracted from the time-of-flight spectra and laboratory angular distributions combined with ab initio calculations propose that the reaction proceeds on the triplet surface via an addition of atomic carbon to the phosphorus atom. This leads to a triplet CPH3 complex. A successive hydrogen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…[41,42] This has been observed, for example, in the reaction of carbon atoms with phosphine (PH 3 ) studied recently in our laboratory. [43] We would like to comment now on the center-of-mass angular distributions. Both distributions were found-within the error limits-to be symmetric around 908.…”
mentioning
confidence: 99%
“…[41,42] This has been observed, for example, in the reaction of carbon atoms with phosphine (PH 3 ) studied recently in our laboratory. [43] We would like to comment now on the center-of-mass angular distributions. Both distributions were found-within the error limits-to be symmetric around 908.…”
mentioning
confidence: 99%
“…34,51 We have computed the relevant stationary points of the triplet state at the G3B3 and other accurate levels, and used the relative energies as reference to define a suitable DFT method; one which provides enough accuracy and is economical enough to make it possible to perform "on the fly" QCT computations. The O3LYP/ 6-31G** method already provides reasonably accurate energies, but we have found that relatively small changes in the functional parameters significantly improve the results; we name the method O3LYP /6-31G**.…”
Section: The "Unimolecular" Step: the Pes Of The Triplet Statementioning
confidence: 99%
“…29 In our view, a thorough study of the C + PH 3 reaction is needed, not only because of its fundamental chemical importance, but also because of astrochemical arguments, even if, to our knowledge, that reaction has not been included in current models so far. [31][32][33] To our knowledge, the only experimental study of the title reaction is that of Guo et al 34 They have employed a crossedbeam technique, and performed the experiment for two collision energies, namely 21.1 kJ/mol and 42.5 kJ/mol. They have also performed electronic structure computations on the potential energy surface (PES) of the [CPH 3 ] system in its lowest triplet electronic state, which allowed them to discuss the molecular reaction mechanism and estimate the lifetimes of the main reaction intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al have studied the potential energy surface of the H 3 CP system (singlet and triplet) using quadratic configuration interaction and coupled‐cluster methods with Pople‐type bases of triple‐z plus polarization quality. Guo et al complemented their crossed‐beamed molecular study of the C( 3 P) + PH 3 reaction with a density functional study of the triplet‐state potential energy surface, including the products, although they also performed single‐point energy computations on the optimized geometries using the coupled‐cluster method with a triple‐z basis set. Kim et al studied the rearrangement of H 2 CPH to H 3 CP (methylphosphinidene) in their lowest singlet and triplet states with a configuration interaction method and basis sets of triple‐z plus polarization quality, providing equilibrium geometries and harmonic vibrational frequencies.…”
Section: Introductionmentioning
confidence: 99%